2014
DOI: 10.1017/s1431927614009350
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Imaging of Lithium Ion Distribution During In Situ Operation of a Battery Electrode and Electrolyte

Abstract: The integration of renewable, and often intermittent, energy sources such as solar and wind into the energy landscape, as well as the electrification of transportation, requires dramatic advances in electrical energy conversion and storage technologies including fuel cells, batteries and supercapacitors. TEM detection of lithium through a liquid is difficult, because lithium is a weak elastic scatterer and multiple scattering from the liquid overwhelms the inelastic core-loss signal in electron energy-loss sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…This study indicates this technique shows promise for visualizing uptake of iron into the bacteria. In situ spectral imaging via EELS 59 or energy dispersive x-ray spectroscopy (EDS) 60 mapping may provide additional means for visualizing iron uptake, which has only been possible to date in dried bacteria samples using techniques like scanning transmission x-ray microscopy 61 . Finally, further correlative fluorescence and fluid cell electron microscopy studies utilizing fluorescent proteins could allow investigation of the connections between biomolecular processes and biomineralization of magnetosome magnetite nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates this technique shows promise for visualizing uptake of iron into the bacteria. In situ spectral imaging via EELS 59 or energy dispersive x-ray spectroscopy (EDS) 60 mapping may provide additional means for visualizing iron uptake, which has only been possible to date in dried bacteria samples using techniques like scanning transmission x-ray microscopy 61 . Finally, further correlative fluorescence and fluid cell electron microscopy studies utilizing fluorescent proteins could allow investigation of the connections between biomolecular processes and biomineralization of magnetosome magnetite nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fast oxidation of Li metal changes the shape, length and mechanical properties of the dendrites, making the results inconclusive. Imaging of lithium dendrite growth using synchrotron-based X-ray tomography 19 and electrochemical liquid transmission electron microscopy holders can potentially be applied for this system 33 , but we decided to look for a simpler method that can be applied consistently to ICMs for many different types of batteries with standard equipment base. Therefore we decided to carry out the study for copper dendrites, which can serve as convenient 'mechanical' proxy of lithium dendrites under ambient conditions.…”
Section: Barementioning
confidence: 99%
“…When Gu et al 63 applied the liquid-cell configuration to study a battery with a Si nanowire electrode (Figure 6a), they not only observed phenomena that are consistent with the open-cell studies but also successfully unraveled the dynamics of the electrolyte, which is difficult to probe using the open-cell setup. 64 Following this pioneering work, Zeng et al 22 observed Li metal dendritic growth and SEI layer formation (Figures 6b and c) 65 used a similar configuration to determine the lithiation state of LiFePO 4 in real time with a relatively high spatial resolution. Beyond these discoveries, the liquid-cell configuration also holds potential for further improvements.…”
Section: Liquid-cell Configurationmentioning
confidence: 99%